L’émergence de l’hôpital « écologique » en Algérie : quels indicateurs retenir ? The Emergence of the "Ecological" Hospital in Algeria: which Indicators to Retain? - Salmi, Madjid; Mohellebi, Samya (Milev Journal of Research and Studies, 2021)
In this paper, we examine the emergence of the ecological hospital and the indicators to be retained to develop a hospital which is responsible toward its environment. Therefore, it contributes in sustainable development by drawing inspiration from literature and experience of advanced countries in the field. Also, we address the evolution of the concept of hospital over time and its different perceptions. Then we discuss the indicators used for the emergence of the ecological hospital which, through its buildings, its various activities as well as its patients, makes the patient a key element acting directly on its immediate environment. Hence, the possibility of listing and classifying classes of indicatorsallowing the emergence of a more ecological hospital.